Neutrophil to lymphocyte ratio in pediatric patients with asthmatic exacerbation and community-acquired pneumonia - Mei Xu; Lingfang Zhou; Jie Zhang; Sha Luo; Yunfeng Zhao; Wei Xiong (BMC, 2023)
Abstract Background Compared with a lower neutrophil to lymphocyte ratio(NLR), a higher one denotes severe asthma exacerbation in hospitalized asthmatic children. In addition, NLR is significantly higher in pediatric patients with community-acquired pneumonia (CAP) than those without. Nevertheless, its role in pediatric patients with concomitant asthmatic exacerbation and CAP remains unknown. Methods In this retrospective study including 1032 pediatric patients aged 5 to 14 years old, the diagnostic and prognostic value of NLR in children with concomitant asthmatic exacerbation and non-severe CAP were investigated. Results The sensitivity and specificity of NLR for a diagnosis of CAP in patients with asthmatic exacerbation were 56.9% and 90.1%, respectively. The cutoff value of NLR for a diagnosis of CAP in patients with asthmatic exacerbation was 4.15 (P < 0.001). The cumulative asthmatic exacerbation during 3-month followup of patients with high NLR were 23 (21.3%) and 58 (42.0%) in the asthma and asthmatic CAP groups, respectively (P < 0.001). The patients with high NLR who had unimproved CAP were 15 (8.3%) and 23 (12.2%) in the CAP and asthmatic CAP groups, respectively (P = 0.006). Multivariate analyses showed that along with the increase of NLR by 1.0 point, the HR for the occurrence of asthmatic exacerbation and unimproved CAP were 2.91 [1.83-3.96] (P = 0.001) and 3.38 [1.66-5.10] (P < 0.001), respectively. Conclusions NLR had high and moderate diagnostic value for the exclusion and indication of CAP, respectively, in pediatric patients with asthmatic exacerbation. It also had prognostic value for the outcomes of pediatric patients with concomitant asthmatic exacerbation and CAP.